ANALISIS YURIDIS TERHADAP SANKSI MALAPRAKTIK MEDIS DI INDONESIA: STUDI LITERATUR ATAS REGULASI DAN IMPLEMENTASINYA - Gunawan Widjaja (CV. ADIBA AISHA AMIRA, 2025)
This study analyses the effectiveness and challenges of enforcing sanctions for medical malpractice in Indonesia through a literature review of regulations and their implementation from criminal, civil, and administrative law perspectives. The study findings indicate that although the legal framework has established criminal, civil, and administrative sanctions for medical malpractice perpetrators, its implementation still faces various obstacles, such as difficulties in proving liability, a heavy burden of proof on patients, unclear definitions of medical malpractice in regulations, and weak coordination and oversight among relevant agencies. Harmonisation of regulations, strengthening the capacity of law enforcement agencies, and developing supporting systems such as electronic medical records are needed to enhance the effectiveness of sanction enforcement and legal protection for both patients and medical personnel.